Recreational abuse of a prescribed medication by an adolescent with attention deficit hyperactivity disorder - İsmail Akaltun; Tayfun Kara (Psychiatry and Clinical Psychopharmacology, 2018)
Methylphenidate (MPH) is one of the most commonly used medical therapeutic options in the treatment of attention deficit hyperactivity disorder (ADHD). We discuss a 14-year-old male adolescent started on MPH in therapeutic doses with a diagnosis of ADHD, who then developed euphoria and rapid tolerance, followed by subsequent abuse of medication. The patient and his family both gave written consent for the publication of this report.